Differences in energy expenditure during high-speed versus standard-speed yoga: A randomized sequence crossover trial. (December 2016) - Potiaumpai, Melanie; Martins, Maria Carolina Massoni; Rodriguez, Roberto; Mooney, Kiersten; Signorile, Joseph F.
Highlights: We evaluated differences in energy expenditure between high- and low-speed yoga. Our results establish that high-speed yoga produces a higher energy expenditure. High-speed yoga may be an effective modality to target cardiometabolic factors. Abstract: Objectives: To compare energy expenditure and volume of oxygen consumption and carbon dioxide production during a high-speed yoga and a standard-speed yoga program. Design: Randomized repeated measures controlled trial. Setting: A laboratory of neuromuscular research and active aging. Interventions: Sun-Salutation B was performed, for eight minutes, at a high speed versus and a standard-speed separately while oxygen consumption was recorded. Caloric expenditure was calculated using volume of oxygen consumption and carbon dioxide production. Main outcome measures: Difference in energy expenditure (kcal) of HSY and SSY. Results: Significant differences were observed in energy expenditure between yoga speeds with high-speed yoga producing significantly higher energy expenditure than standard-speed yoga (MD = 18.55, SE = 1.86, p < 0.01). Significant differences were also seen between high-speed and standard-speed yoga for volume of oxygen consumed and carbon dioxide produced. Conclusions: High-speed yoga results in a significantly greater caloric expenditure than standard-speed yoga. High-speed yoga may be an effective alternative program for those targeting cardiometabolic markers.